Diagnostic Insights for Optimal Avanza/Xenia AC Performance: Wawasan Diagnostik untuk Performa AC Avanza/Xenia yang Optimal - Utomo, Indra Bhekti (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the AC system of Avanza/Xenia vehicles through diagnostic procedures aimed at identifying potential issues and ensuring adherence to maintenance standards. The air conditioning (AC) system in vehicles plays a pivotal role in ensuring driver and passenger comfort, necessitating regular monitoring and maintenance. Utilizing measuring tools such as compressors and multimeters, the main components including the magnetic clutch and evaporator were assessed. Results indicate that measured values, including magnetic clutch coil resistance (3.9 ohms), magnetic clutch gap (0.5 mm), and blower system resistance (ranging from 0 to 2.6 ohms), fall within acceptable service limits outlined in the Avanza/Xenia manual. Consequently, no repair procedures were deemed necessary, affirming the normal condition and suitability for use of the AC system. This research fills a knowledge gap by providing a systematic diagnostic approach for evaluating vehicle AC systems, offering implications for maintenance practices in ensuring optimal performance and longevity. Highlights: Routine maintenance prolongs AC system lifespan. Accurate diagnosis prevents potential issues. Component inspection ensures system health. Keywords: PMCB, Vehicle Air Conditioning System, Maintenance, Repair, Troubleshooting